Bibelen som kulturarv: The Cultural Turn i eksegesen - Buch-Hansen, Gitte (Dansk Teologisk Tidsskrift, 2024)
Abstract: This article combines a review of The Nordic Bible: Bible Reception in Contemporary Nordic Societies (2023) with a brief discussion of the book. The eleven case studies draw attention to the culturalization which increasingly characterizes the status and use of the Bible in the secular Nordic countries. The analyses demonstrate how the invocation in the public debate of biblical phrases, proverbs and parables typically neglect the original, scriptural context. Thus, the pastoral power of the Bible may be activated by referring to a shared – minimal – knowledge of the book, but still presupposes a shared acknowledgement of its sacred status. This development has taken place at the same time as the population in the Nordic countries has moved away from the romantic idea of the oneness of the nation – one language, one religion, one race, one land – to a new complex national multiplicity. However, the rich analyses of the book also call for national minority groups’ response to this attempt to buckle up the Bible for the majority’s national identity project.